Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s00417-012-2118-1
|View full text |Cite
|
Sign up to set email alerts
|

Decreased retinal sensitivity and loss of retinal nerve fibers in multiple system atrophy

Abstract: MSA patients feature significant reduction in nasal RNFLT and global mean deviation when compared to healthy controls, consistent with the multi-systemic nature of this neurodegenerative disorder. This finding provides first evidence for two independent deteriorations of the visual system in MSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
4
10
0
2
Order By: Relevance
“…Our results confirm that the macular ganglion cells (GCC) and their axons, that is, the RNFL are affected in patients with MSA . Our cross‐sectional study showed that patients with MSA had a significant reduction in the global as well as in the inferior RNFL quadrant of the peripapillary retina.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results confirm that the macular ganglion cells (GCC) and their axons, that is, the RNFL are affected in patients with MSA . Our cross‐sectional study showed that patients with MSA had a significant reduction in the global as well as in the inferior RNFL quadrant of the peripapillary retina.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, in patients with MSA, a rare fatal adult‐onset synucleinopathy, preliminary imaging studies have identified a significant reduction in retinal nerve fiber layer (RNFL) thickness . This finding appeared unexpectedly because patients with MSA have no clinical visual complaints.…”
mentioning
confidence: 99%
“…Another study in 2013 evaluated 12 patients with MSA and 10 age-matched healthy controls (54). The study did not find differences in foveal thickness or global RNFL.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, the acquisition protocol of macular measurements (e.g., image resolution, number and dimension of slices, analyzed areas from those slices, layers analyzed, and segmentation methods) varied considerably among studies, and in some studies certain macular measurements were not reported.The statistical analysis of the OCT results was markedly different: most studies averaged the results of both eyes (51, 5456); two considered the results of each eye as independent values (50, 52), whereas one study used only the results of the right eye (53). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation